Assistance in preparing financial reports for digital-based MSME actors in Tungkal Ilir Sub-District - Utami Mizani Putri; Khairiyani Khairiyani; Kurniyati Kurniyati; Chintia Putri Wulandari (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
Having good and correct financial reports using the Financial Accounting Standards for Micro, Small, and Medium Entities for MSMEs makes a benchmark for representing how the ongoing business performance is so that it can determine the future direction of the business smoothly The method used in this Community Service Activity (CSA) is Participatory Action Research (PAR). There are three main pillars of the PAR method, starting from the research methodology, the action dimension, and finally the participation dimension. The evaluation results of the implementation of activities for two days showed that the participants were very enthusiastic about making and preparing financial reports by utilizing the menu in the MSME Business Financial Records Application (Toko Ku). Participants can also utilize the report menu which consists of sales reports, expense reports, profit/loss reports, and general reports. These reports are outputs from menus such as cash, products, inventory, sales, receivables, payables, and expenses.